Using Magic Cube and a Modified LSB for Audio Steganography - Salim Mohammed, Nuha; Tariq Mustafa Al-Ta'I, Ziyad (International Journal of Engineering and Technology, 2018)
This paper introduces randomness-based audio steganography with magic square and magic cube cryptography methods that are respectively based on (LSB) or Least Significant, with National institute of Standards and Technology(NIST)and enhancement of LSB audio steganography.This enhancement is based on the mathematical foundations of the magic squareby using three algorithms with any order or any size. Magic square is a branch of mathematical combinatorics. It is one of the different arrays in magic number arrangements. The new proposed technique focuses on normal magic cubes of order from (3to n). The values inside the designed magic cube are used as an index to audio cover locations. These scrambled locations (according to the keys of magic cube) in audio cover are used to LSB embed secret text message. In order to increase the security of the proposed system, the starting number, the difference value, the dimension, and the values inside the magic cube are kept as a secret key. The National institute of Standards and technology (NIST) package is successfully used to test the randomness of the magic cube's keys values. peak signal to noise ratio (PSNR) of audio stegocovers are(62.65743352-79.57336476) dB in which the size of secret text message (256-16) bits.Â Â Â